2009
DOI: 10.1088/0004-637x/700/2/1262
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Line Survey of the Extreme Carbon Star CRL 3068 at Millimeter Wavelengths

Abstract: We present the results of a molecular line survey of the extreme carbon star CRL 3068. The observations were carried out with the Arizona Radio Observatory (ARO) 12 m telescope and the Heinrich Hertz Submillimeter Telescope (SMT) at the λ 2 mm and λ 1.3 mm atmospheric windows. The observations cover the frequency bands from 130 to 162 GHz and 219.5 to 267.5 GHz. The typical sensitivities achieved are T R < 15 mK and T R < 7 mK for the ARO 12 m and SMT, respectively. Seventy-two individual emission features bel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…To investigate this problem, more carbon stars must be surveyed at wider wavelength ranges. In our previous works (Zhang et al 2009a(Zhang et al , 2009b, we have obtained the λ1.3 mm and 2 mm spectra of CIT 6 and CRL 3068 using the Arizona Radio Observatory's 12 m and 10 m Submillimeter Telescopes, and found that the chemical compositions of both sources are similar to that of IRC+10216. More evolved carbon stars that have been studied through line surveys include the PPN CRL 2688 (Park et al 2008), the PPN CRL 618 (Pardo et al 2007), and the young PN NGC 7027 (Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…To investigate this problem, more carbon stars must be surveyed at wider wavelength ranges. In our previous works (Zhang et al 2009a(Zhang et al , 2009b, we have obtained the λ1.3 mm and 2 mm spectra of CIT 6 and CRL 3068 using the Arizona Radio Observatory's 12 m and 10 m Submillimeter Telescopes, and found that the chemical compositions of both sources are similar to that of IRC+10216. More evolved carbon stars that have been studied through line surveys include the PPN CRL 2688 (Park et al 2008), the PPN CRL 618 (Pardo et al 2007), and the young PN NGC 7027 (Zhang et al 2008).…”
Section: Introductionmentioning
confidence: 96%
“…However, such studies have hitherto only focused on a few bright evolved stars or a small number of molecular species. For this reason, we have been performing a long-term project of systematic spectral line surveys of a large sample of evolved stars at wide wavelength ranges (He et al 2008;Zhang et al 2008Zhang et al , 2009aZhang et al , 2009b. The present paper is the fifth one of this series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…⋆⋆ The FITS file containing the fully reduced spectrum presented in this paper is available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.u-strasbg.fr/cgi-bin/qcat?J/A+A/. ing single-dish telescopes have been presented for high-massloss-rate, carbon-rich AGB stars: IRC +10 216 (Cernicharo et al 2000(Cernicharo et al , 2010, CIT 6 (RW LMi; Zhang et al 2009a), and CRL 3068 (LL Peg; Zhang et al 2009b). Patel et al (2011) presented an interferometric survey of IRC +10 216 obtained with the Submillimeter Array (SMA).…”
Section: Introductionmentioning
confidence: 99%
“…The proximity of IRC +10216 to us (∼ 130 pc) and the relatively large mass loss rate (∼ 2 × 10 −5 M yr −1 ) makes it to be the prototype of AGB star and justifies the extensive observational studies carried out on it. Spectral line surveys have however been performed on other C stars such as CIT 6, observed with the 12-m ARO and SMT telescopes by Zhang et al (2009a) in the frequency ranges 131-160 GHz, 219-244 GHz, and 252-268 GHz, and CRL 3068, which has been surveyed with the same telescopes by Zhang et al (2009b) in the frequency ranges 130-162 GHz and 219.5-267.5 GHz. These two objects, CIT 6 is located at ∼ 400 pc and has a mass loss rate of ∼ 3 × 10 −6 M yr…”
mentioning
confidence: 99%